2020
DOI: 10.1101/2020.07.24.216374
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

NT3/TrkC pathway modulates the expression of UCP-1 and adipocyte size in human and murine adipose tissue

Abstract: NT3, through activation of its tropomyosin-related kinase receptor C (TrkC), modulates neuronal survival and neural stem cell differentiation. It is widely distributed in peripheral tissues (specially vessels and pancreas) and this ubiquitous pattern suggests a role for NT3, outside the nervous system and related to metabolic functions. The presence of the NT3/TrkC pathway in the adipose tissue (AT) has never been investigated. Present work studies in human and murine adipose tissue (AT) the presence of elemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…As recently reviewed in [ 71 ] (and references therein), in a developing brain, neurotrophin-3 and its TrkC receptor are involved in synaptogenesis, but their levels dramatically decrease with brain maturation. In contrast, NT-3 and its TrkC receptor are widely distributed in peripheral tissues, such as blood vessels, heart tissue, AT, pancreas tissue and skeletal muscle tissue.…”
Section: Metabotrophic Factors As Therapeutic Targets In Drug Discoverymentioning
confidence: 99%
“…As recently reviewed in [ 71 ] (and references therein), in a developing brain, neurotrophin-3 and its TrkC receptor are involved in synaptogenesis, but their levels dramatically decrease with brain maturation. In contrast, NT-3 and its TrkC receptor are widely distributed in peripheral tissues, such as blood vessels, heart tissue, AT, pancreas tissue and skeletal muscle tissue.…”
Section: Metabotrophic Factors As Therapeutic Targets In Drug Discoverymentioning
confidence: 99%
“…An accompanying editorial concluded that "the potential therapeutic utility of ADR β3 for cardiometabolic disorders is down, but it's not yet out" (37). There are yet questions to be answered along with their potential role as a supplement to the synergy of other pathways for metabolic and mental health (38)(39)(40)(41)(42)(43)(44).…”
Section: Summing Up and Conclusionmentioning
confidence: 99%